432 ADOPTIVE TRANSFER OF DIABETOGENIC AUTOAGRESSIVE CD40+ T CELLS INDUCES ENDOTHELIAL DYSFUNCTION IN NOD.SCID MICE. (1st January 2005) - Wiktor, A. J.; Flores, N.; Wagner, D.; Waid, D.; Anobile, B.; Flores, S. C.
Abstract : Vascular complications due to diabetes mellitus occur despite adequate euglycemic control in some patients. Previously we demonstrated that a vascular NADPH oxidase-dependent oxidative stress leads to endothelial dysfunction in non-obese diabetic (NOD) mice prior to overt diabetes. This dysfunction manifests as a paradoxical vasoconstriction in response to the vasodilator acetylcholine (Ach). As type I diabetes results from autoimmune destruction of the pancreatic beta cells, we addressed the role of the immune system in the paradoxical vasoconstriction. We isolated thoracic aortae from euglycemic NOD, from diabetes-resistant non-autoimmune BALB/c and from the diabetes-resistant severely combined immunodeficient (NOD.scid) mice. We segmented the aortae into rings and measured isometric force in response to cumulative doses of Ach. In contrast to rings from NOD mice, rings from NOD.scid mice showed no vasoconstriction, behaving like BALB/c mice. Since the NOD.scid is genetically identical to the NOD mouse, but lacks T or B cells, these findings suggest that an intact immune system must be present for endothelial dysfunction to occur. In order to further dissect the immune components responsible, CD4+/CD40+ or CD4+/CD40- T cells were isolated from NOD mice and adoptively transferred into NOD.scid mice. The CD40+ cell population is autoimmune-prone and able to transfer diabetes. Surprisingly, all aortic rings isolated from mice that received the CD40+, but not from mice that received the CD40- cells showed the paradoxical vasoconstriction, suggesting that the endothelial dysfunction seen in the NOD could be adoptively transferred as well. We also found that expression of NADPH oxidase subunits p47 and p67 phox was elevated in NOD.scid/CD40+ mouse hearts when compared to NOD.scid/CD40- and NOD.scid mice. Furthermore, the acetylcholine-induced paradoxical vasoconstriction seen in NOD.scid/CD40+ isolated aortic rings was prevented by dyphenyleneiodonium, a non-specific NADPH oxidase inhibitor. Ex vivo transduction with a recombinant adenovirus expressing a transdominant negative p67 phox subunit inhibited the paradoxical vasoconstriction seen in NOD mice, further implicating NADPH oxidase in NOD endothelial dysfunction. These findings suggest that endothelial dysfunction is not a direct result of the hyperglycemia, but rather, an autoimmune-mediated phenomenon which occurs in conjunction with the pathogenesis of Type I diabetes.